2019
DOI: 10.1080/02656736.2019.1578420
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and bioinformatic analysis of condyloma acuminata: mild hyperthermia treatment reveals compromised HPV infectivity of keratinocytes via regulation of metabolism, differentiation and anti-viral responses

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Proteomic and bioinformatic analysis of condyloma acuminata: mild hyperthermia treatment reveals compromised HPV infectivity of keratinocytes via regulation of metabolism, differentiation and anti-viral responses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In terms of absorptivity and penetration depth, the red light of 635 nm is the most commonly used clinical light source. At present, LED light source is widely used [ 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of absorptivity and penetration depth, the red light of 635 nm is the most commonly used clinical light source. At present, LED light source is widely used [ 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local hyperthermia decreases enzymes and molecules related to keratinocyte differentiation in wart tissue, such as KRT5, KRT27, KRT75, KRT76, and H2AFY2, and inhibits proteins involved in cellular metabolism, such as GALT, H6PD, EXOSC4, and EXOSC6; conversely, it promotes the expression of proteins involved in antiviral processes, such as OAS1, MX1, BANF1, CANX. 10 In addition, local hyperthermia also promotes the maturation of Langerhans cells and induces a systemic anti-HPV immune response, thus leading to the regression of lesions at unirradiated sites as well. 11 Jiang et al reported a case of periungual warts in a 9-year-old child successfully treated with local hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, T cellular immunity plays significant roles in the activation of HPV and the occurrence, cure, and relapse of CA. In addition, previous studies have reported the existence of cellular immunity dysfunction in CA patients, 13,14 including disproportional peripheral blood T lymphocyte subsets, an abnormal rate of natural killer cells, and an imbalance of cellular factors, for example, interleukins. These aberrations of cellular immunity will eventually protect the virus from immune system attack.…”
Section: Discussionmentioning
confidence: 99%